Pengolahan Keuangan dan Aset Daerah Bengkulu Tengah District - Putri, Sudriyanti; Edwarman, Edwarman (Jurnal Adminitrasi Bisnis Nusantara, 2024)
The purpose of this study is to analyze the collection and reporting system tax fund restaurant or restaurant in the DPPKAD Bengkulu Tengah District. Data analysis method used is descriptive analysis method with the type of Comparative (comparison). The results showed that the procedures for payments made by DPPKAD Bengkulu Tengah District have fit the decree with regulation Bupati Bengkulu Tengah Distict No. 40 of 2012 this can be seen from the way the payment of fees or taxes restaurants and restaurants based STPD received by a resident Taxes and Taxpayers pay the bill in a lump sum each month to the cashier DPPKAD Bengkulu Tengah District. Then after making the payment cashier will issue SSPD (Tax Payment Region) as evidence of taxpayer has made tax payments resotran and restaurants. The procedure for tax collection of restaurants and eating houses conducted by DPPKAD Bengkulu Tengah District not fit the decree regulation Bupati Bengkulu Tengah Distict No. 40 2012. This is due to the many obstacles that cause still difficult implemented a system of sanctions or fines. Comparison between reporting tax restaurants and restaurants by DPPKAD Bengkulu Tengah District with the uykfNo. 40 of 2012 Middle compliance. It can be seen from the dilkukan deposit by cash to the treasurer DPPKAD every day and preparing reports for accountability has been done by the treasurer DPPKAD